E-166 Middle meningeal artery embolization for chronic subdural hematomas: predictors of treatment failure from large US multicenter experience. (23rd July 2022) - Salem, M; Lang, M; Hoang, A; Baig, A; Khorasanizadeh, M; Baker, C; Cortez, G; Hanel, R; Tanweer, O; Kan, P; Levy, E; Grandhi, R; et al.
Abstract : Introduction: Middle meningeal artery (MMA) embolization has emerged as a promising treatment option for chronic subdural hematoma (cSDH) patients, with reportedly lower recurrence rates compared to conventional open surgery. However, little remains known regarding predictors of treatment failure. Therefore, identification of these predictive factors would be of paramount importance to optimize patient selection for the success of these procedures. Methods: A series of consecutive patients undergoing MMA embolization for chronic subdural hematomas at 9 North American centers (2018–2021) were included and analyzed. Treatment failure was defined as hematoma reaccumulation or neurological deterioration requiring rescue surgery, either during the same initial admission or on post-operative follow-up (i.e., 90 days from treatment procedure). A multivariate logistic regression model was constructed utilizing potentially significant variables (i.e., p<0.2) on univariate analysis and literature-known potential confounders to identify predictors of treatment failure (i.e., requiring rescue surgery). Results: A total of 534 patients undergoing 624 embolization procedures (mean age 72 years, 27.2% females) were included, with 90 patients undergoing bilateral embolizations (16.9%). On presentation, median admission cSDH thickness was 15.6 mm (IQR 11–20), with 31.4% and 22.2% of patients were on antiplatelet and anticoagulation medications, respectively. Failure of therapy requiring rescue surgery was encountered in 37 patients (6.7%; median follow-up 4.6 months). On multivariate analysis controlling for confounders including age, gender, concurrent surgical evacuation, presence of midline shift >5 mm, hematoma thickness >10 mm, pre-treatment baseline antiplatelet/anticoagulation therapy, independent predictors of treatment failure were pre-treatment anticoagulation therapy (OR 3.4; 95% CI: 1.4–8.1; p=0.006) pre-treatment antiplatelet therapy (OR 2.3; 95% CI 1.06–5.2; p=0.036), and concurrent surgical evacuation (OR 2.3; 95% CI 1.03–5.3; p=0.042). Conclusions: In this cohort, the independent predictors of MMA embolization failure requiring reintervention were pre-treatment baseline anticoagulation and antiplatelet therapy, and concurrent surgical evacuation. These factors might help guide individualized treatment selection and counseling in patients undergoing this procedure. Disclosures: M. Salem: None. M. Lang: None. A. Hoang: None. A. Baig: None. M. Khorasanizadeh: None. C. Baker: None. G. Cortez: None. R. Hanel: None. O. Tanweer: None. P. Kan: None. E. Levy: None. R. Grandhi: None. B. Gross: None. A. Siddiqui: None. C. Ogilvy: None. M. Lang: None. A. Thomas: None. B. Jankowitz: None. J. Burkhardt: None.